El otorgamiento del registro de servicios para operadores del cable submarino, a personas del derecho privado, y su relación con un presunto monopolio en la implementación de internet fijo por fibra óptica en el Ecuador - Bekich Feraud, Juan Miguel (2020)
In recent years, telecommunication and internet services have been evolving and eveloping new technologies at high speed, so the country saw the need to collaborate with private companies, specialized in technology and telecommunications, in order to supply the users from all over the country, providing a better fixed internet service to citizens with better quality at a lower price. For this reason many media began to be interested in the subject, to understand the operation of this internet business through fiber optics. At the time of the purchase of submarine fiber optic cables (investment made by a private company and with the help of the government), legal professionals and citizens in general misunderstood the purchase of the same, generating doubt and instability, leading them to speculate on a possible monopoly of fiber optic internet in the country…….